Peran Herbal Medicine dalam Pencegahan Gangguan Neuro-Oftalmologis, Psikiatrik, dan Toksikologi Forensik : Suatu Kajian Sistematik - Ardizal Rahman; Hengky Ardian; Agung Wijayanto; Dwi Wijayanti (The Journal General Health and Pharmaceutical Sciences Research, 2023)
Neuro-ophthalmological, psychiatric, and toxicological disorders caused by exposure to toxic substances represent a growing global health concern. Preventive approaches using herbal medicine have gained attention due to their relatively favorable safety profiles and broad pharmacological benefits. This study aims to investigate the effectiveness of herbal medicine in preventing disorders across these three domains, based on the latest scientific literature. The review was conducted following the PRISMA 2020 guidelines, with literature searches performed through PubMed, Scopus, and ScienceDirect using keyword combinations such as "herbal medicine," "prevention," "neuro-ophthalmology," "psychiatry," and "toxicology." A total of 27 studies met the inclusion criteria. The findings reveal that certain herbal plants, including Ginkgo biloba, Curcuma longa, and Melissa officinalis, possess neuroprotective, antioxidant, and anxiolytic properties. In conclusion, herbal medicine holds promising potential as part of a preventive strategy against neuro-ophthalmological, psychiatric, and forensic toxicological disorders, although further research is needed to achieve standardization and clinical validation.